ANALISIS TINGKAT ANTUSIAS SISWA SEKOLAH DASAR DALAM MENGIKUTI PROGRAM GERAKAN LITERASI SEKOLAH (GLS) - Oktaviani, Seli; Fitriyah, Sefti; Indriati Widyaningsih, Yennie (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The School Literacy Movement (GLS) in elementary schools is a strategic program aimed at fostering a literacy culture and increasing students’ interest and engagement in reading and writing activities at the elementary school level. However, in practice, students’ level of enthusiasm in participating in the GLS program still varies and has not been fully optimal. This study aims to analyze the level of enthusiasm of elementary school students in participating in the School Literacy Movement (GLS). This research employed a quantitative approach with a descriptive survey design. The research subjects were 30 fourth-grade students of SDN 7 Sukamentri. Data were collected using a closed-ended questionnaire with a Likert scale developed based on indicators of enthusiasm, including response, attention, concentration, willingness, and awareness to be involved. The data were analyzed using descriptive statistics through percentage techniques and categorization. The results showed that 53% of students were in the high enthusiasm category, 43% in the moderate category, and 4% in the low category. These findings indicate that, in general, students have demonstrated a high level of enthusiasm in participating in the GLS program, particularly in the 15-minute reading activity before lessons. Nevertheless, some students still showed moderate and low levels of enthusiasm, indicating the need for improved consistency in program implementation, greater variation in literacy activities, and more optimal teacher guidance. Thus, the GLS program has been proven to play a positive role in developing a literacy culture in elementary schools.